Equivalence after extension and Schur coupling do not coincide on essentially incomparable Banach spaces. Issue 6 (18th October 2019) - ter Horst, S.; Messerschmidt, M.; Ran, A. C. M.; Roelands, M.
Abstract: In 1994, H. Bart and V. É. Tsekanovskii posed the question whether the Banach space operator relations matricial coupling (MC), equivalence after extension (EAE) and Schur coupling (SC) coincide, leaving only the implication EAE/MC ⇒ SC open. Despite several affirmative results, in this paper we show that the answer in general is no. This follows from a complete description of EAE and SC for the case that the operators act on essentially incomparable Banach spaces, which also leads to a new characterisation of the notion of essential incomparability. Concretely, the forward shift operators U on ℓ p and V on ℓ q, for 1 ⩽ p, q ⩽ ∞, p ≠ q, are EAE but not SC. As a corollary, SC is not transitive. Under mild assumptions, given U and V that are Atkinson or generalised invertible and EAE, we give a concrete operator W that is SC to both U and V, even if U and V are not SC themselves. Some further affirmative results for the case where the Banach spaces are isomorphic are also obtained.